Produksi Blok Plastik Bahan Pasangan Dinding dari Kombinasi Plastik Tipis Bekas Kemasan dan Minyak Jelantah Tanpa dan Dengan Pengisi Abu Sekam - Thanaya, I Nyoman Arya; Mataram, I Nyoman Karnata; Ian Anu, Dafry (Rekayasa, 2025)
Waste thin plastic wrap in the form of crackle plastic, aluminium coated plastic, other thin plastics, have not yet been widely utilized. Limited un-organic rubish collector willing to receive it. The price is also relatively low, hence it is not attractive for it’s collection. This material can be used as a plastic wall block (PWB) with combination of those waste plastic, waste cooking oil (wco), without and with rice husk ash filling. The objective was to analyze the properties of the PWB. There were four mixed produced namely: Mix A (50% crackle plastic+25% aluminium coated plastic+25% other thin plastics and wco); Mix B: (75% crackle plastic+12.5% aluminium coated plastic+12.5% other thin plastics and wco). Mix C: similar to Mix A, added with rice husk ash. Mix D, similar to mix B, added with rice husk filling. The samples were produced by heating the wco at 200 °C, the the waste plastic were melted without and wirh rice husk ash, then pressed at around 576.02 kg. The mixture were pressed at 100-125 °C. It was obtained that the density: 0.796 – 0.817gr/cm3, porosity: 0.018 – 0.096, IRS: 0.015 – 0.045 kg/cm2.minute, absorption: 0.044– 0.169%. The unsoaked compressive strength was 14.51 – 27.285  kg/cm2. The soaked one was 13.005 – 23.205. In general the compressive strength obtained was within higher range of low quality block experimented by researchers in some part of the world with sttength between 2.55-15.2 kg/cm2.